СТВОРЕННЯ ЧАГАРНИКОВИХ УГРУПОВАНЬ ЯК ОСЕРЕДКІВ ВІДНОВЛЕННЯ БІОРІЗНОМАНІТТЯ ЖОВТОКАМЯНСЬКОГО КАР’ЄРУ (Ecological Bulletin of Kryvyi Rih District, 2024)
The completion of mining in open-pit mines raises the issue of their  further use. It is important to ecologically restore such areas, create habitats for plant and animal communities, and restore biodiversity. The non-operational part of the Zhovtokamianska quarry  has a depleted species composition of shrubs. New species of shrubs and shrub communities will create additional habitats for plant and animal species and help restore the quarry's biodiversity. Within the non-operational part of the Zhovtokamianka open pit, we have identified five areas with environmental habitats that meet the biological properties of shrub species. Based on the criteria of drought resistance, frost resistance, viability, flowering and fruit ripening periods, trophicity, and the possibility of use by fauna, 8 shrub species were selected for planting within these areas.According to the criteria, the following species were selected for planting: White snowberry (Symphoricarpos albus (L.) Blake). Japanese kerria (Kerria japonica (L.) Dc.), Common privet (Ligustrum vulgare L.), European euonymus (Euonymus europaeus L.), Japanese spiraea (Spiraea japonica L.f.), Tatar honeysuckle (Lonicera tatarica L.), Zvehinzov lilac (Syringa sweginzowii Koehne & Lindl.), Cossack juniper (Juniperus sabina L.). In 2018, 33 plants of these species were planted. All species successfully completed the growing season of 2018, but 90.9% of plants (30 out of 33 specimens) took root in the new location. 2 plants of Syringa sweginzowii Koehne & Lindl. and 1 plant of Euonymus europaeus L. died. Surveys in 2019-2021 revealed that all shrubs are in good condition, passing through the stages of flowering and fruiting (with the exception of Juniperus sabina L., which is vegetating). The planted shrub species are beautifully flowering early spring and ornamental plants, have improved the aesthetic perception of the territory of the idle part of the Zhovtokamianskyi open pit and, together with shrub species of natural flora, have become a habitat for habitat, feeding and reproduction of various groups of wildlife - arachnids, insects, reptiles, birds and mammals. The fruits and seeds of the shrubs will continue to spread to new areas, both within the open pit and adjacent to it, increasing their biodiversity.  The created shrub communities will help increase the gene pool of wild flora, accelerate the processes of self-renewal of tree, shrub and herbaceous vegetation to the zonal type.
Keywords: biodiversity, shrubs, Zhovtokamyansky quarry